A study on awareness among professionals towards the importance of building surveying profession in Malaysian construction industry / Syafirul Azie Abu Samah - Abu Samah, Syafirul Azie (Faculty Architecture, Planninng and Surveying, 2014)
The Building Surveying profession in Malaysia was in its early period of existence. Up to present date, Building Surveying field has been established approximately 24 years since 1990. Despite the long period of establishment, Building Surveyor profession is not really be recognized in Malaysia, which resulting to unawareness on the importance of this profession and misunderstood by Professionals in Malaysian construction industry. This research is aimed to study and investigate the levels of awareness among professionals towards the importance of Building Surveying profession in Malaysian construction industry. Taking into account the Building Surveying profession development and current status in Malaysia and the level of awareness towards the importance of Building Surveying Profession among professional in Malaysian construction industry. The methodologies for this research are based on the literature review and survey by distributing questionnaire among Professionals who are working with government and private sectors. The nonexistence of specific Act Regulated to support the profession was found to be the main reason on why Building Surveyor’s entitlement to its specific post and recognition among Malaysian construction industry. The Building Surveyor Act was drafted with the aim of providing statutory recognition of the profession in 2007. But, until today the teams of the BS division of RISM have not gained any approval for the Act and this has contributed to the delay in the enactment of this legislation. It can be conclude that the Act is very important because by having the Act, Building Surveying profession will be well known as a professional profession in the construction industry in Malaysia and will be recognized by the public